Effects of marine reserves on the biology of rocky intertidal limpets along the southern coast of South Africa - Nakin, Motebang Dominic Vincent (Rhodes University, Faculty of Science, Department of Zoology and Entomology, 2009)
Limpets are harvested by people in South Africa, but are selected in terms of species and size. The effects of marine reserves on the biology of commonly exploited (Helcion concolor and Scutellastra longicosta) and rarely exploited species (Cellana capensis and Scutellastra granularis) were investigated on the southeast coast of South Africa at two reserve and two non-reserve sites. For each species, a 4-way nested ANOVA was used to test the effects of month, reserve, site (nested within reserve) and area (nested within site and reserve) on population density, size structure and recruitment of these limpets. The data were collected monthly over 20 months. The overall results indicated a gradient of exploitation among species, S. longicosta was the most heavily exploited species and S. granularis the least exploited species. However, there was also a gradient of exploitation between reserves and non-reserves. Xhora was the most heavily exploited site while Nqabara was less heavily exploited. Of the two reserve sites, Cwebe had more poachers than Dwesa. In most analyses, the month x area (reserve (site)) interaction was significant. However, this was largely an artifact due to comparisons of areas in different sites and significant differences between areas within sites occurred in relatively few months. Densities were greater inside reserves for all species except C. capensis. For S. longicosta and H. concolor this was expected but not for S. granularis and the result possibly reflects its opportunistic exploitation in the absence of the preferred species or indirect effects of reserves. Commonly exploited species and the rarely exploited C. capensis clearly showed greater mean and maximum sizes in reserves but there were month/site (reserve) interactions. Months with significant differences between reserves and nonreserves in both mean and maximum sizes generally occurred more often for commonly exploited than rarely exploited species, but C. capensis showed the strongest reserve effect on maximum size. Interview surveys showed that, although not normally exploited, C. capensis is sometimes mistaken for H. concolor and this suggests that large individuals are unintentionally harvested outside reserves. There were no significant reserve effects on recruitment for any species. Although Xhora had the lowest densities and limpet sizes, it showed the highest recruitment especially for S. longicosta, suggesting that larvae can be transported far from where they are released and settle in non-reserve sites regardless of adult densities. Reserve as a main factor was not significant for the rarely exploited species, but there was a significant month x reserve interaction, with non-reserves having greater GSI values than reserves in most months. Growth rates were examined using individual tagging and cohort analysis. The two techniques gave different results, with individual tagging giving higher growth estimates than cohort analysis. Except for the territorial species S. longicosta, growth was higher in non-reserves and inversely correlated with population density. Mortality estimates using the Cormack-Jolly-Seber model indicated that the rarely exploited species had significantly greater capture probabilities in reserves while no significant reserve effects were observed for the commonly exploited species. Reserve effects on survival probability were significant only for S. longicosta, with reserves being greater than nonreserves and no significant effects for any other species. Enhanced survival in reserves was attributed to the effects of human exploitation. In theory, marine protected areas show increases in densities, sizes and reproductive output of exploited species, but the present results revealed that the efficacy of reserves depends on the status of the species, not only whether it is exploited or non-exploited, but also whether it is territorial.
Keywords: Limpets; Marine parks and reserves -- South Africa; Marine biology -- South Africa